Exploring barriers to rehabilitation for individuals with spinal cord injury: a qualitative study in Iran - Farhad Nosrati Nejad; Mehdi Basakha; Abdurrahman Charkazi; Abdullatif Esmaeili (BMC Health Services Research, 2025)
Abstract Objectives Rehabilitation services are crucial for improving the quality of life and overall health of individuals with spinal cord injuries (SCIs). However, access to adequate rehabilitation remains limited in many regions, including Iran. This study aims to explore the barriers faced by individuals with SCIs in accessing appropriate rehabilitation services within Golestan province, northern of Iran. Methods This study employed a qualitative approach to explore the barriers experienced by individuals with SCIs in accessing rehabilitation services. Fourteen participants were purposefully selected from the Golestan province (north of Iran) until data saturation was reached. Semi-structured interviews were conducted during the summer and fall of 2023, recorded, transcribed, and subjected to rigorous thematic analysis. Results The study identified three primary categories of barriers: 1) Personal limiting factors, such as insufficient health literacy and inadequate home adaptations; 2) provider-related, including insufficient expertise, non-professional service delivery, inappropriate facility adaptations, limited service accessibility, and inadequate service provision; and 3) socio-supportive, encompassing companionship needs, financial constraints, insurance limitations, and bureaucratic hurdles. Conclusion The findings of this study highlight a complex interplay of patient, provider, and societal factors that impede access to rehabilitation services for individuals with spinal cord injuries in Golestan province. While provider-related challenges are prevalent, the significance of individual and socio-supportive factors cannot be overstated. To optimize rehabilitation outcomes, a holistic approach is essential, addressing not only physical impairments but also psychosocial and environmental barriers. The findings of this study underscore the complex interplay of patient, provider, and societal factors that influence access to rehabilitation services for individuals with spinal cord injuries. While provider-related challenges, such as insufficient expertise and limited service accessibility, are significant, the study emphasizes the crucial role of individual and socio-supportive factors in facilitating successful rehabilitation. Addressing these multifaceted barriers requires a holistic approach that considers not only physical impairments but also psychosocial and environmental needs.